Berenstain Bears (The)/ : and Too much tv - Berenstain, Jan (New York : Random House, 1984)
Concerned that the family is spending too much time in front of the television and neglecting other activities, Mama Bear decides that there will be no television watching for one week.
Keywords: Television - Fiction; Bear -- Fiction